Serum antineuronal antibodies in patients with post-COVID-19 condition − association to intensive care - Posharina, Tatiana; Varonen, Mikko; Jarva, Hanna; Kanerva, Mari; Liira, Helena; Laakso, Sini M (Elsevier BV, 2026)
Post-COVID-19 condition (PCC), characterized by persistent symptoms following SARS-CoV-2 infection, is a global health challenge. Neurological symptoms are common in PCC, and immune-mediated mechanisms have been proposed as potential contributors. We set out to systematically explore serum antineuronal antibodies in patients with PCC and clinical factors associated with seropositivity. Our prospective, single-center cohort study included adult patients with a confirmed SARS-CoV-2 infection at least three months prior and a diagnosis of PCC. Serum and cerebrospinal fluid (CSF) samples were analyzed for the presence of antineuronal antibodies. A control group with confirmed SARS-CoV-2 infection but without PCC symptoms was included, age-, sex- and time from acute infection to sampling -matched to seropositive cases of PCC. Among 314 consecutive patients with PCC, 38 (12.1 %) tested positive for serum antineuronal antibodies. CSF analysis was performed for a subset; however, no intrathecal autoantibodies were detected. The most prevalent serum autoantibodies targeted CASPR-2 (n = 7, 18.9 %), neurofascin-186 (n = 5, 13.2 %), and glycine receptor (n = 4, 10.8 %). Multinomial logistic regression identified intensive care unit (ICU) admission during acute COVID-19 as the only significant predictor of autoantibody positivity (OR 3.4; 95 % CI: 1.0-10.4). Of the 35 control subjects, two (5.7 %) tested seropositive: one with low titer myelin oligodendrocyte glycoprotein antibodies and another with borderline myelin antibody levels. None of the patients met criteria for autoimmune encephalitis, and neurological assessments and brain magnetic resonance imaging were unremarkable. Neuropsychological testing showed a trend toward impairments in attention and executive functions among seropositive individuals. Thus, there was no significant difference in the prevalence of serum antineuronal antibodies in PCC compared to post-infection controls, and the association between seropositivity and ICU admission suggested systemic immune activation rather than a specific autoantibody-mediated mechanism. It remains unclear whether observed neuropsychological deficits are attributable to autoantibodies or the effects of critical illness.